2022
DOI: 10.1007/s11259-022-09901-y
|View full text |Cite
|
Sign up to set email alerts
|

Milk proteins as mastitis markers in dairy ruminants - a systematic review

Abstract: Mastitis is one of the most impacting diseases in dairy farming, and its sensitive and specific detection is therefore of the greatest importance. The clinical evaluation of udder and mammary secretions is typically combined with the milk Somatic Cell Count (SCC) and often accompanied by its bacteriological culture to identify the causative microorganism. In a constant search for improvement, several non-enzymatic milk proteins, including milk amyloid A (M-SAA), haptoglobin (HP), cathelicidin (CATH), and lacto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 77 publications
0
14
0
1
Order By: Relevance
“…The most convenient and commonly used indirect method is probably the California mastitis test, which is based on the visual evaluation of the milk viscosity following addition of a reactive [ 9 , 10 , 11 ]. Otherwise, measuring milk electrical conductivity [ 6 , 12 , 13 ], or the identification of protein biomarkers (e.g., interleukins, lactoferrin, cytokines, amyloid A, haptoglobin) using enzyme-linked immunosorbent assay method could help to identify the presence of inflammation [ 14 ]. However, all these methods are not useful to identify the causative pathogens that cause the CM or SCM.…”
Section: Introductionmentioning
confidence: 99%
“…The most convenient and commonly used indirect method is probably the California mastitis test, which is based on the visual evaluation of the milk viscosity following addition of a reactive [ 9 , 10 , 11 ]. Otherwise, measuring milk electrical conductivity [ 6 , 12 , 13 ], or the identification of protein biomarkers (e.g., interleukins, lactoferrin, cytokines, amyloid A, haptoglobin) using enzyme-linked immunosorbent assay method could help to identify the presence of inflammation [ 14 ]. However, all these methods are not useful to identify the causative pathogens that cause the CM or SCM.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, individual milk samples were collected from a total of 120 primiparous Holstein Friesian cows during routinely mastitis screening tests and subjected to MALDI-TOF MS analysis to detect peptide/protein profiles suggestive of the subclinical form of the disease. Indeed, bovine mastitis is able to modify the milk proteome and several proteins have been reported to be differently abundant during mammary gland inflammation ( 12 ). To compare healthy subjects with cows potentially affected by subclinical mastitis, the milk samples were classified according to the SCC measurement, setting the 200,000 cell/ml value as a threshold.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to SCC, another parameter that could be investigated and correlated to mammary gland inflammation is the protein composition of milk ( 12 ). During mastitis, milk proteins are enriched by host immune proteins, such as cytokines, acute phase proteins, chemokines, and lactoferrin, but also by bacterial enzymes, mainly proteases ( 12 , 13 ). Several studies have explored the potentiality of protein biomarkers as alternative/integrative diagnostic tools by means of different approaches ( 13 16 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, a comparative test showed that this diagnostic tool’s applicability is limited, and its accuracy is lower compared to other methods, such as the California mastitis test [ 117 , 126 , 127 ]. Other possible biomarkers for mastitis diagnosis, such as procalcitonin (PCT), neopterin (NPT), haptoglobin (HP), serum amyloid A (SAA), proinflammatory cytokines (IL-1β, IL-8, TNF-α, IF-γ) [ 128 , 129 , 130 , 131 , 132 , 133 ], as well as lactose [ 70 ] are now the subject of research and analysis.…”
Section: On-farm and Lab Methods For Monitoring Udder Health And Milk...mentioning
confidence: 99%